Competition Authorities in South Eastern Europe Building Institutions in Emerging Markets - Begović, Boris; Popović, Dušan V. (Contributions to Economics, 2018)
This open access book provides answers to key open questions concerning competition policy in emerging economies, with a focus on South Eastern Europe. The contributions address two major issues. One is the design of competition policy and the national competition authorities that enforce it, including the topics of competition advocacy and state aid control; the other is the use of economic methods in competition law enforcement, especially in the cases of relevant market definition and merger control. Many lessons learned in the countries of South Eastern Europe can be applied to the emerging markets of other regions. As such, the findings presented here will be highly relevant for officials and staff at national competition authorities, advisers to legislators shaping national competition policy, competition law professionals, and university students alike. ; Presents topical insights into the institutional design of national competition authorities Offers specific economic methods relevant for competition law enforcement Linked to a dedicated website providing information about ongoing competition law cases in SEE countries